2019
DOI: 10.3389/fneur.2019.01015
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Experimental Rodent Models of Repeated Blast TBI

Abstract: We reviewed the relevant literature delineating advances in the development of the experimental models of repeated blast TBI (rbTBI). It appears this subject is a relatively unexplored area considering the first work published in 2007 and the bulk of peer-reviewed papers was published post-2011. There are merely 34 papers published to date utilizing rodent rbTBI models. We performed an analysis and extracted basic parameters to capture the characteristics of the exposure conditions (the blast intensity, inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Third, our findings are based on one histopathological (i.e., silver staining) and three immunohistochemical analyses (i.e., GFAP, Iba-1, and NeuN staining). We selected these analyses because they allowed for the evaluation of different brain cells (i.e., neurons, astrocytes, and microglia) that are known to be affected by blast exposure 26 , 32 , 44 , 45 . Nonetheless, we acknowledge that analyses based on other proteins or techniques may reveal additional contributions to changes in the brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our findings are based on one histopathological (i.e., silver staining) and three immunohistochemical analyses (i.e., GFAP, Iba-1, and NeuN staining). We selected these analyses because they allowed for the evaluation of different brain cells (i.e., neurons, astrocytes, and microglia) that are known to be affected by blast exposure 26 , 32 , 44 , 45 . Nonetheless, we acknowledge that analyses based on other proteins or techniques may reveal additional contributions to changes in the brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous approaches, which have not to date so much addressed blast research, have shown how complex sex difference studies can be, and-consequently-strong experimental design is critical to what may be small but significant experimental effects. The majority of publications related to neurobiological effects have employed laboratory shock tubes using compressed gases (40,196). This will be the emphasis in the discussion below.…”
Section: Preclinical Modeling Of Blast For the Study Of Sex Differencmentioning
confidence: 99%
“…However, the majority of translational TBI work employing both male and female animals has been performed with more severe and/or surgically invasive TBI models such as controlled cortical impact [CCI; e.g., (30)(31)(32)(33)(34)(35)], fluid percussion injury [FPI; e.g., (36,37)], or repetitive concussive brain injury [CBI; e.g., (38,39)]. Although blast injury models have been studied in male animals of many species (23,40), there is a near absence of female inclusion in blast models of neurotrauma.…”
Section: Introductionmentioning
confidence: 99%
“…Research in rat models of repetitive low level blast exposure has shown that animals exposed to repetitive low-level blast exhibit chronic cognitive impairment and PTSD-related traits that develop over time [ 30 , 33 , 100 , 101 , 123 ]. These traits include anxiety, enhanced acoustic startle, altered fear learning and impaired cognition in tests such as novel object recognition.…”
Section: Introductionmentioning
confidence: 99%